Kajian Pelatihan Digitalisasi Pada UMKM Binaan Melalui Program Teman Kreasi PT Smartfren Telecom. Tbk - Wibowo, Susilo; Hubeis, Musa; Sarma, Ma'mun (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2023)
PT Smartfren Telecom, Tbk with its corporate social responsibility (CSR) program has established a forum called "Teman Kreasi". Teman Kreasi Smartfren has been running for seven years. This CSR program has a mission to develop a spirit of co-creation and social entrepreneurship for the younger generation, as well as to open opportunities for the growth of creative MSMEs in various areas. The Smartfren Community is located. and has reached 52 cities in Indonesia. Currently, there are 1,085 SMEs, whereas 70% of which are located in Java, Sumatra, Sulawesi, and Kalimantan.This research was conducted to examine the benefits experienced by the mentored SMEs, as well as to provide input for future activities. Generally, the research was conducted to evaluate the digitalization training provided by the Teman Kreasi program. The Strength, Weakness, Opportunities, Threats (SWOT) method, Analytic Hierarchy Process, and Training Need Assessment (TNA) approach were used to obtain strategic improvements and provide feedback for future training programs. The evaluation of the digital training activities of the mentored SMEs by Teman Kreasi Smartfren concluded that the training was very good and should be continued. Furthermore, there was a significant difference in the sales of the SMEs before and after receiving the training. The training led to an increase in sales and a shift from conventional sales to digital sales through marketplaces to expand sales coverage. Additionally, collaborating with influencers was found to be effective in providing direct promotion impact on social media users.